CODESRIA Bulletin Online, No. 5, July 2020 - Structural Change, Inequality and Inclusive Development: Case of Sub-Saharan Africa - Jimi O. Adesina (CODESRIA Bulletin, 2020)
Introduction Explaining Africa’s development and well-being has become something of an industry, advancing explanations that range from geography to malaria (Gallup et al. 1999, Gallup and Sachs 2001), genetic diversity (Ashraf and Galor 2013), and neopatrimonialism. It is un- certain what policymakers should make of the claims in these stud- ies: move their countries to more auspicious locations? If as Ashraf and Galor (2013) suggest, a 1 per cent reduction in Ethiopia’s genetic diversity would raise per capita income by 27 per cent, would that involve eliminating some of the citizens? Ashraf and Galor’s proposition has been much celebrated and critiqued, and none more so in the latter category than Tang (2016), who demonstrated the invalidity of the genetic diversity hypothesis. Neopatrimonialism’s flattening of the African political landscape fails to explain the role of ‘strong men’ in Ethiopia vis-à-vis Equato- rial Guinea, or the diversity in economic and social outcomes across time and space in the region, and would equate Mandela and Nyerere with Mobutu Sese Seko or Idi Amin (Mkandawire 2015). Diver- gences in social and economic performances across time and space point to the importance of policy, leadership, and institutions. In this contribution, we examine the experiences of Sub-Saharan Africa with economic development and the challenge of structural transformation of the econo- mies. We further explore the pattern of inequality across differ- ent domains—wealth, education, health, habitat, and gender. We end with some indications of policy directions for enhancing inclusive development in the region. Structural Change and Economic Development While there has been considerable scepticism about the development project on account of its impulses, cost, and feasibility (or even desirability), the prospect of ‘catch-up’ (and socio-economic development broadly) continues to animate the global policy environment, and in the ‘developing world’ more so. The sceptical position, illustrated by Escobar (1995), ascribes the development impulse to Harry Truman; a “dream [that] was not solely the creation of the United States but the result of the specific historical conjuncture at the end of the Second World War” (Esco- bar 1995: 4). Valid as it may be, there is a different impulse for the development aspiration, which is epitomised by the spirit of the 1955 Bandung Conference of Asian and African states (Mkandawire 2011). The aspiration is borne out of the humiliating experience of colonial conquest, the optimism of the im- mediate post-colonial era, the need to create autonomous spaces with- in the global order, and to enhance economic transformation and human capability. In the African con- text, these impulses are captured in policy frameworks ranging from the Lagos Plan of Action (1980) to Agenda 2063 (2015). At the heart of these frameworks is a funda- mental (structural) transformation of African economies, underpinned by “industrialisation, manufacturing and value addition” (AU 2015: v) as the basis for the sustained improvement of the well-being of the population. The Lagos Plan of Action, a culmination of four years of consultation and drafting (Adedeji 2002: 37), was triggered by what was seen as a relatively weak performance of African economies, the persistence of colonial structure of production, and disillusion with the ‘trickle- down’ approach to development. Over the period 1960 to 1975, Africa’s aggregate annual GDP growth rate was 4.5 per cent instead of the target of 6 per cent set in the UN Second Development Decade. Exports grew at 2.8 per cent instead of the target of 7 per cent. On the other hand, import grew at an an- nual average of 10 per cent instead of the target of 7 per cent (Adesina 2006). The African Union’s Agen- da 2063 takes up the aspirations that underpinned the Lagos Plan of Action and the ‘nationalist’ devel- opment intentions. In between the two periods have been several socio-economic interventions but none more profound and enduring than the neoliberal turn in the policy framing of the economic, social, and political agenda. It set in motion, from the early 1980s, a fundamental shift in Africa’s development trajectory— rolling back of the state, denun- ciations of industrial policy, and a long period of mass entitlement failure on the continent, especially in the Sub-Saharan African region. What it did not do, though, was address the structural problems identified in the Lagos Plan of Action. In addition to the lost decades, the effect has been what Mkandawire (2005) referred to as the maladjustment of African economies. In broad terms, the composition of Sub-Saharan Africa’s GDP has changed little between 1965 and the 2010s (cf. Figure 1), although this belies the size of the economies, the shifting rates of growth, the policy impetuses that underpinned growth performance at different phases over the period, and diversity of specific country-level composition of GDP.3 The contribution of the manufacturing value-added in Sub-Saharan Africa to the GDP declined from 17.86 per cent in 1976 to 11 per cent in 2012, before a slight increase to 11.23 per cent in 2014. The recovery from 16.3 per cent in 1978 to 17.04 per cent in 1980 was offset by a continuous decline after 1980.4 Figure 1: Sub-Saharan Africa—Sectoral Contribution to GDP (%) ( Voir PDF) Source: World Bank Africa Development Indicators Database (2020 online).2 A key feature of Sub-Saharan Africa’s GDP is that it was always dominated by the Service sector, which rose from 46.96 per cent in 1965 to 58.38 per cent in 2014, although across time the composition varied. Financial services and the telecommunication industries play an increasing role in the sector and driving growth (World Bank 2015). Rather than a manufacturing sector-led structural change in the economy, the intensive high skill segments of the services sector are driving change. This has implications for inequality and inclusive development, which we discuss in the next two sections. At the other end is the expansion in the informal economy. Its share of non-agricultural employment grew from 67.3 per cent in the 1980-84 period to 86.9 per cent in the 1995-99 period before declining to 65.9 per cent in the 2005-10 period (Charmes 2012). There is, of course, considerable variation between countries in the region. The percentage of persons employed in the informal sector (as a share of non-agricultural activities) ranged from 9.3 per cent in Mauritius to 71.4 per cent in Mali (ILO 2012). Over half of the gross value added (GVA) in the region’s non-agricultural GVA came from the informal sector in the 2000s (Charmes 2012). In the same period, the combined GVA for the informal sector and agriculture was 63.6 per cent. This speaks to the dual-track trajectory of economies in the region: a high-investment, high-skill segment and a low-skill, low-investment segment, the latter being the abode of most of the poor, with considerable implications for deepening inequality. The adverse impact of orthodox neoliberal policies deployed in the region can be assessed from the trend in per capita GDP, measured in constant 2005 US dollars (cf. Figure 2). After a steep rise from 1960 to 1974, when the region’s per capita GDP rose to US980.63, it went into a steep decline after 1980 (to US769.31 in 1994). It was not until 2010—more than two-and-half decades later—that it recovered to the 1974 level. Again, there are significant inter-country variations across the region. Per capita GDP does not tell us much about the well-being of people in an economy, and there is no one- to-one relationship between GDP growth rate or per capita GDP and citizens’ well-being. However, the relative translation into well-being and inequality between the periods before and after the early 1980s is instructive. Robust social policy instruments help in translating growth into well-being; especially with active labour market policies, expansive social investment, and public social provisioning. Often, these measures reflect the health of an economy. In the medium to long terms, a healthy economy is essential for sustaining robust and equitable social policy instruments. If we exclude South Africa, the growth rate of the region’s GDP rose from 0.4 per cent in 1961 to 10.4 per cent in 1970, 8.3 per cent in 1974, and an average of 5.9 per cent between 2004 and 2008. The average growth rate from 1980 to 1985 was 1 per cent, with contractions in 1981 and 1983. Figure 2: Sub-Saharan Africa GDP per capita (Constant 2005 US) (Voir PDF) Source: World Bank World Development Indicators Database (2016). Growth would remain unsteady until 1995. More dramatic is the trend in gross domestic savings as a percentage of GDP over the period 1960 to 2011, which experienced a steady increase from 20.4 per cent in 1960 to 25.17 per cent in 1980 to a sharp decline after that (cf. Figure 3). Even with small recoveries, the region has not recovered to anywhere near the level in 1980, much less surpass it. After the more recent narratives of “Africa Rising” (The Economist 2011)—which followed an earlier claim of Africa as ‘The hopeless continent” (The Economist 2000)—the emerging fiscal and balance of payment difficulties, and the resurgence of public debt, in a growing number of African coun- tries speak to the structural weaknesses of the more recent growth path. They talk of the increasing urgency of the structural transformation of the region’s economies based on manufacturing-driven industrialisation. In successive reports since 2013, the UN Economic Commission for Africa reiterated the need for economic transformation based on job-enhancing industrial strategy (UNECA 2013, 2014, 2015). The emphasis in the 2016 report is on green industrialisation, which significantly changes the direction and composition of the economies without harming the environment (UNECA 2016). The same vision underpins the African Union’s Agenda 2063. Figure 3: Sub-Saharan African Gross Domestic Saving (% of GDP) (Voir PDF) Source: World Bank Africa Development Indicators Database Online (2020).5 Inequality and the challenge of inclusive development6 There is broad consensus that average economic inequality in sub-Saharan Africa is among the highest in the world. Inequality has remained higher in sub- Saharan Africa, in the period from the 1960s to the late 2000s, than the rest of the world, except Latin America. Broadly, income inequality declined from the early 1960s to 1980 (Milanovic 2003, p.10). Ravallion and Chen (2012) suggest that average income inequality rose from 1981 to 1990, declining between 1990 and 1996 before rising between 1996 and 2008. In each case, income inequality in sub-Saharan Africa was only lower than in Latin America. However, the average rate of income inequality and the trend hide significant variation in the region. The ratio of the income share of the top 10 per cent relative to that of the bottom 10 per cent for the period between 1995 and 2014 ranged from 1 to 6.62 in Niger (2011) to 1 to 51.22 in South Africa (2011) (African Development Bank 2015). The share of the top 10 per cent in total income ranges from 25.83 per cent in Mali (2010) to 53.78 per cent in South Africa (2011). The countries with the highest income Gini indices are concentrated in Southern Africa. Using per capita consumption expenditure data for the period 1991/3 to 2011, Cornia and Martorano (2015) found four distinct trends in 29 sub-Saharan African countries with at least four observation data points. In thirteen countries, the Gini trend declined between 1991/3 and 2011. Four countries registered an inverted U-shape trend in which the Gini index rose before falling. In seven countries, the Gini index rose over the period. In the last group of five countries, the Gini trend took a U shape, with income inequality declining before rising over the period. Of the 29 countries, Ethiopia (2011) had the lowest Gini index at 33.6, while the Gini for Botswana (2009) and South Africa (2011) were 68.6 and 65.0, respectively. It is crucial, however, to know that consumption data are not a good measure of income inequality, much less wealth or asset inequality. Consumption data hides the discretionary incomes and assets of the better off in society. A more graphic picture of inequality emerges when we consider wealth inequalities. Again, Africa’s7 wealth inequality level is only second to that of the Asia- Pacific region8 (at 89.2). The coun- tries with the highest wealth Gini index include South Africa (84.0), Botswana (81.7), Namibia (81.6), and Nigeria (81.4), all mineral resource-rich countries. In the field of education, between 1999 and 2011, sub-Saharan Africa registered improvements in several indicators—from net enrolment ratio in primary school (58% to 77%) to gender parity (0.85 to 0.93), respectively. However, the region lagged behind other regions of the world, and between-country indicators vary widely. Across the region in 2012, 16.6 million girls and 13 million boys in the primary school age cohort were out of school (UNESCO 2015). In Nigeria in 2013 a child from the poorest quintile was over 23 times more likely never to have been in school compared with a child from the richest quintile; nine times in Ghana in 2011; twice in South Africa in 2013. In the area of health, between 1990 and 2012, sub-Saharan Africa witnessed improvements in several indicators, although at levels lower than the global average. Again, there are variations across countries in the region (WHO 2014). While rising across the region, life expectancy at birth varied from 74 years in Cape Verde, Mauritius, and Seychelles to 46 years in Sierra Leone. The three island states are also countries with some of the most developed social policy architectures in the region. Again, while the infant mortality rate declined across the region between 1990 and 2012, the rate varied: from 13 per thousand live births in Seychelles to 182 in Sierra Leone. In Nigeria, much more than spatial location and education level of mothers, wealth inequality is the main driver of health inequality: DTP39 immunisation coverage is more than eight times lower in the poorest quintile than in the richest quintile. At the same time, there is parity or near parity at very high levels of coverage (between 89% and 99%) in immunisation between these quintiles in Burundi and Rwanda (WHO 2014). Across several indicators, wealth, spatial location (rural/urban), and the educational level of mothers are the main drivers of health inequalities (WHO 2014). But underlining these drivers is the extent of the engagement of public authorities in promoting and facilitating the wellness of the citizens. While national-level inequality matters, especially rural-urban inequality, intra-city inequality tends to be higher than national level in- dices (UNHABITAT 2010, 2014). The highest levels of urban income inequalities are found in South Africa’s major cities, generally above 7 Gini index with Pointe-Noire in Congo recording the lowest income inequality. Using consumption-based measures, Lomé (Togo) recorded the lowest Gini index at 3, with Maputo and Addis Ababa at over 5 (UNHABITATA 2010: 27). There is a better visual marker of the incidence of urban inequality than the slums in many of the region’s urban areas. The size and growth path of slum-dwelling differ across the region. Between 1990 and 2010, countries such as Mali, Ghana, South Africa and Ni- geria have seen declines in the proportion of urban dwellers that live in slums, while the percentage in Kenya remained steady at 55 per cent. By contrast, countries such as Malawi, Mozambique, and the Central African Republic have seen increases in the proportion of urban dwellers living in slums—to 70 per cent, 81 per cent, and 96 per cent, respectively. However, even for countries that experience declines in the share of urban dwellers liv- ing in slums, the absolute number is hardly comforting. For Nigeria and South Africa, for instance, the absolute number of slum dwellers rose from 33 million to 79 million, and from 19 million to 30 million, respectively (UNHABITAT 2010: 29). The implications of state re- trenchment, informal sector location, unemployment and under- employment for slum-dwelling are significant, and these speak as well to the challenge of inclusive devel- opment in the region. Gender inequality deserves distinct exploration and here The Global Gender Gap Report (2014) pro- vides a snapshot of the gender gap in sub-Saharan Africa along four domains: economic participation and opportunity, educational attainment, health and survival, and political empowerment. As with other aspects of inequality, there is enormous between-country variation in the region. Rwanda, Burundi, and South Africa are the three top-performing countries on the overall gender gap index, with Cote d’Ivoire, Mali, and Chad being the worst three performers. However, the performance of countries varies across the sub-indexes. In 2015, Rwanda ranked highest in political empowerment, boosted by being the country with the highest percentage of female legislators in the world: 63.8 per cent of its parliamentarians are women (In- ternational Parliamentary Union 2015). Burundi, with a score of 0.86, topped the global sub-index for economic participation and opportunity, followed by Malawi (0.829), Botswana (0.816) and Kenya (0.81). The disparity in gender gap scores highlights the point that gender parity in education, for instance, does not automatically translate into gender equality in other domains. Globally and across the region social institutions (norms, practices, and law) remain critical drivers of gender inequality (OECD 2015). Here again, policy and leadership matter; the degree of mitigation of gender inequality is often a result of focused activism and strong public leadership. In search of Inclusive Development Sub-Saharan Africa’s recent growth performance has had divergent impacts on poverty and inequality across countries in the region. In countries like Uganda and Ethiopia, the poverty rate has declined significantly. Across the region, however, the number of people in absolute poverty10 nearly doubled between 1981 and 2015—from 210.4 million to 419.6 million, while those living below the 2.5/day (or 3.10/day) poverty line increased from 319 million in 1981 to 675.8 million in 2011.11 Similar to the level of inequality, the poverty level underscores the challenge of inclusive development. A particularly glaring feature of the ‘Africa rising’ (Afrique emergente) phase is the abysmally low growth elasticity of poverty—the percentage reduction in poverty rates associated with a percentage growth of per capita income. The initial stress on growth and market transactional path to securing well- being produced neither growth nor secured well-being. In more recent times, the accent has been on social assistance in mitigating chronic poverty—ranging from unconditional cash transfers to public works-based programmes. Important as these programmes are in ameliorating poverty, the transfers involved, as the World Bank (2014) acknowledged, are “insufficient to lift [people] out of poverty.” Transfers generally cover between 12 per cent (Lesotho) and 27 per cent (Zambia) of beneficial households’ income or consumption,12 and outside Southern Africa are mostly donor- financed. Sustainable, inclusive development would need to transcend the current narrow focus on poverty (Mkandawire 2010); it would require raising the productive capacity of people in the country, increased social investment (health and education), redistribution, with a focus of addressing gender inequalities. Addressing productivity issues would require in rural areas a focus on smallholder farmers: enhancing their productive capacity, investment in infrastructure, including upstream and downstream support for agricultural production. Countries such as Ethiopia, Uganda, and Rwanda that man- aged to match economic growth with poverty reduction, as Arndt et al. (2016) noted, paid attention to improving smallholder farmers’ productivity. The industrialisation strategies would need to address multiple tasks at the same time: linking agricultural produce with intermediate industries, labour- intensive manufacturing sectors that expand employment with a focus on decent work. The expansion of employment opportunities will need to focus on reducing employment informality, upgrad- ing informal sector production capacity, and linking them to larger production enterprises. Exploiting national and regional markets is the first step in what would be an extended journey in assessing the global market. Connected to the above will be a renewed emphasis on social investment in health and education, broad and gradual extension of social protection coverage, with a focus on universalism. These would require vastly enhanced state capacity for planning, coordination, and implementation. The idea that geography or genetics predisposes towards abysmal levels of human well-being and economic performance not only runs against human experience but fails to explain the diversity of experiences within Sub-Saharan Africa. Human agency, policy, and leadership matter in advancing inclusive development. Notes An earlier version of this article was prepared for the Division of Social Policy and Development of the UN Department of Economic and Social It was present- ed at an inter-agency expert group meeting on “Employment and de- cent work for poverty reduction, in support of the Second United Nations Decade for the Eradica- tion of Poverty (2008-2017)” in Bangkok, Thailand (4-6 May 2016). This is a revised and up- dated version of the earlier paper. Africa Development Indicators Databank (Online version). Avai- lable at https://databank.world- org/source/africa-develop- ment-indicators. (Accessed 27 June 2020). For our analysis, we have used the World Bank’s Africa Development Indicators (ADI) database (rather than the World Development Indi- cators (WDI) database), in spite of the limitations. Primarily, the time series we need end in 2011. In contrast, the time series in WDI start in 1970, while data is avai- lable till 2018. The WDI dataset makes it difficult to differentiate sufficiently the Sub-Saharan Afri- ca’s performances across three critically distinct phases: (a) 1960 and the late 1970s, (b) the lost decades of 1980 to 2000, and (c) the period since The prima- ry observation is that, across the three phases, the performances have an ‘N’ shape. This is most evident in the per capita GDP time series (Figure 2). We use data from the Africa De- velopment Indicators database for Figure 1 because of the mis- sing data for the period before 1976 in the World Development Indicators Africa Development Indicators Databank (Online version). Avai- lable at https://databank.world- org/source/africa-develop- ment-indicators. (Accessed 27 June 2020). This section draws in part on Ade- sina (2016. ‘Inequality in Sub-Sa- haran Africa: domains and dri- vers’), prepared for the ISSC World Social Science Report 2016. The Global Wealth Data- book (2015) covers 52 African countries, 47 of which are in sub- Saharan Asia-Pacific minus China and India. Three doses of diphtheria-teta- nus-pertussis vaccine. 1.25/day or 1.90 from October World Bank Poverty and Equity Database. Available at: http:// worldbank.org/ poverty/region/SSF. (Accessed 27-06-2020). Malawi Social Cash Transfer Pro- gram Baseline Evaluation Report (2014).